Change in clinical knowledge of diabetes among primary healthcare providers in Indonesia: repeated cross-sectional survey of 5105 primary healthcare facilities - Stein, Dorit T.; Sudharsanan, Nikkil; Dewi, Shita; Manne-Goehler, Jennifer; Witoelar, Firman; Geldsetzer, Pascal (BMJ Open Diabetes Research & Care, 2020)
Introduction Indonesia is experiencing a rapid rise in the number of people with diabetes. There is limited evidence on how well primary care providers are equipped to deal with this growing epidemic. This study aimed to determine the level of primary healthcare providers’ knowledge of diabetes, change in knowledge from 2007 to 2014/2015 and the extent to which changes in the diabetes workforce composition, geographical distribution of providers, and provider characteristics explained the change in diabetes knowledge. - Research design and methods In 2007 and 2014/2015, a random sample of public and private primary healthcare providers who reported providing diabetes care across 13 provinces in Indonesia completed a diabetes clinical case vignette. A provider’s diabetes vignette score represents the percentage of all correct clinical actions for a hypothetical diabetes patient that were spontaneously mentioned by the provider. We used standardization and fixed-effects linear regression models to determine the extent to which changes in diabetes workforce composition, geographical distribution of providers, and provider characteristics explained any change in diabetes knowledge between survey rounds, and how knowledge varied among provinces. - Results The mean unadjusted vignette score decreased from 37.1% (95% CI 36.4% to 37.9%) in 2007 to 29.1% (95% CI 28.4% to 29.8%, p<0.001) in 2014/2015. Vignette scores were, on average, 6.9 (95% CI −8.2 to 5.6, p<0.001) percentage points lower in 2014/2015 than in 2007 after adjusting for provider cadre, geographical distribution, and provider experience and training. Physicians and providers with postgraduate diabetes training had the highest vignette scores. - Conclusions Diabetes knowledge among primary healthcare providers in Indonesia decreased, from an already low level, between 2007 and 2014/2015. Policies that improve preservice training, particularly at newer schools, and investment in on-the-job training in diabetes might halt and reverse the decline in diabetes knowledge among Indonesia’s primary healthcare workforce.